Tuberculosis - Pereira, Paulo Camara Marques [UNESP]; Corrêa, Camila Renata [UNESP]; Calvi, Sueli Aparecida [UNESP] (Taylor & Francis, 2014)
Tuberculosis (TB) has been present in man since pre-historic times. More than 100 yr after Robert Koch identified its causative agent in 1882, TB is still a chronic infection with one of the highest morbidity and mortality rates (Brasil-Ministerio da Saude 2002).